THE EFFECT OF USING BAAMBOOZLE EDUCATIONAL GAME MEDIA ON STUDENTS' MOTIVATION TO LEARN SCIENCE IN GRADE V UPT SD NEGERI 130 MATTAROPURAE, BONE DISTRICT - Muliadi Muliadi; Rosmalah Rosmalah; Andi Nurfathimah Zahrah (Sains Global Institut, Indonesia, 2026)
The problem in this research is the low motivation to learn Natural and Social Sciences of fifth grade students in elementary school. This research is a pre-experimental type of quantitative research which aims to determine the effect of using the educational game media Baamboozle on motivation to learn Natural and Social Sciences in class V. The research design used was one group pre-nontest post-nontest with a sample size of 16 students selected based on the NonProbability Sampling technique. The data collection techniques used were pre-nontest and post-nontest in the form of a questionnaire. Data analysis techniques were carried out using descriptive and inferential statistical analysis. Based on the results of data analysis, before using Baamboozle media, the average student pre-nontest score was 50.94, which was in the low category, and after using Baamboozle media, students' learning motivation increased with a post-nontest average of 70.38, which was in the high category. The results of the hypothesis test show a significance smaller than 0.05 at the 5% significance level. The conclusion of this research is that the use of the educational game media Baamboozle has a positive and significant effect on the motivation to learn Natural and Social Sciences of class V UPT students at SD Negeri 130 Mattaropurae, Bone Regency.